2014
DOI: 10.1007/s00467-014-2987-0
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C in acute kidney injury diagnosis: early biomarker or alternative to serum creatinine?

Abstract: Background Early accurate acute kidney injury (AKI) diagnosis is needed to pursue AKI treatment trials. We evaluated Cystatin C (CysC) as an early biomarker of serum creatinine (SCr)-AKI and as an alternative to define AKI. Methods 160 non-cardiac children admitted to our intensive care unit (ICU) were prospectively studied. We measured daily CysC and SCr. AKI was staged according to the Kidney Disease: Improving Global Outcomes (KDIGO) SCr criteria and by similarly applied criteria, using CysC (CysC-AKI) We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 53 publications
5
40
0
1
Order By: Relevance
“…In this observational study, we found that sCysC levels measured on the first day of admission were a powerful predictor for AKI and the short-term prognosis of CCU patients. These findings are consistent with previous results that have been reported in two other clinical studies [36, 37]. More importantly, despite evidence that β2-micro globulin is useful for predicting prognosis in kidney disease, cardiovascular outcomes and death [38-40], the performance of sCysC in predicting AKI and short-term prognosis was superior to β2-micro globulin in our study.…”
Section: Discussionsupporting
confidence: 83%
“…In this observational study, we found that sCysC levels measured on the first day of admission were a powerful predictor for AKI and the short-term prognosis of CCU patients. These findings are consistent with previous results that have been reported in two other clinical studies [36, 37]. More importantly, despite evidence that β2-micro globulin is useful for predicting prognosis in kidney disease, cardiovascular outcomes and death [38-40], the performance of sCysC in predicting AKI and short-term prognosis was superior to β2-micro globulin in our study.…”
Section: Discussionsupporting
confidence: 83%
“…This result was similar to findings in other studies (22)(23)(24). None of the serum indicators, however, showed a significant correlation with mortality.…”
Section: Discussionsupporting
confidence: 82%
“…Another study has reported that the sensitivity and specificity of serum cystatin C for diagnosing AKI are 73.9 % and 78.9, respectively, using 0.6 mg/l as the cutoff value (6) . Similarly, a study conducted by Lagos-Arevaldo et al [18] on pediatric patients admitted to a PICU has reported that serum cystatin C has more diagnostic accuracy than serum creatinine and a greater predictive value for clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%